Microbiological Study on Supply Water and Treated Water in Dhaka City (Stamford Journal of Microbiology, 2011)
Water borne diseases are the major cause of morbidity and mortality in developing countries like Bangladesh, where disease outbreaks occur due to unsafe drinking water, inadequate sanitation and poor hygienic practices. The objective of this study was to evaluate the quality of water used for drinking as well as household purposes in Dhaka city, Bangladesh. Eighteen water samples were collected from different rivers and canals. Among those, two samples were treated with chlorine. Physico-chemical parameters (pH, salinity, turbidity, conductivity and dissolved oxygen) were monitored during the time of sample collection using portable meters. For microbiological analysis, water samples were collected in sterile screw capped bottle. All Experiments were carried out within 24 hours after collecting the samples. All the water sources were found to be contaminated with total coliform, faecal coliform, Escherichia coli, Klebsiella spp., Salmonella spp., Shigella spp., Vibrio cholerae, Aeromonas spp. and Fungi except treated water samples. Several biochemical tests were performed for confirmation of suspected organisms. According to these results, huge amount of total coliform and faecal coliform were observed in every sample and these amount were very much similar for other organisms. Treated water samples were found to be microbiologically accepted than untreated water samples. DOI: http://dx.doi.org/10.3329/sjm.v1i1.9132    Stamford Journal of Microbiology, Vol.1(1), July 2011, p.42-45